Digital literary cartography and colonial space: re-mapping spatial imaginations in Robinson Crusoe and Max Havelaar - Fitriya Dessi Wulandari; René Faruk Garzozi Pincay; Dian Muhammad Rifai (Asosiasi Relawan dan Pengelola Jurnal LPTNU (ARJUNU), 2026)
Background: The spatial turn in literary studies and digital humanities highlights the need to reassess how colonial space is constructed through the interaction between narrative and cartographic knowledge. Objective: This study examines how colonial spatial imagination is produced, contested, and differentiated in Robinson Crusoe (1719) and Max Havelaar (1860) through digital literary cartography. Method: Using a qualitative digital humanities design, the research integrates close textual analysis with historical cartographic materials and spatial metadata, focusing on Atlantic navigation maps, West Indies and New England coastal maps, and administrative maps of Java and Bantam. Results: The findings show that Robinson Crusoe aligns with a cartographic logic of enclosure and maritime circulation, reinforced by island, Atlantic, and West Indies maps that normalize spatial mastery. In contrast, Max Havelaar articulates a fragmented administrative geography, revealed through maps of Java and the Dutch East Indies that expose bureaucratic segmentation and ethical tension. Comparative re-mapping demonstrates divergent cartographic epistemologies shaped by exploration versus governance. Implication: Digital literary cartography reveals colonial space as an ideological construct rather than a neutral backdrop. Novelty: The study offers a comparative Global South–oriented cartographic reading that repositions maps as critical epistemic texts in colonial literature.